Coffee Biomass-Based Carbon Material for the Electrochemical Determination of Antidepressant in Synthetic Urine - Barreto, Francisco Contini [UNESP]; Mounienguet, Naelle Kita [UNESP]; Ito, Erika Yukie [UNESP]; He, Quan; Cesarino, Ivana [UNESP] (MDPI, 2024)
Escitalopram (ESC) is commonly prescribed as an antidepressant to enhance serotonin levels in the brain, effectively addressing conditions such as depression and anxiety. The COVID-19 pandemic, along with ongoing mental health crises, has exacerbated the prevalence of these disorders, largely due to factors such as social isolation, fear of the virus, and financial difficulties. This study presents the enhancement of a glassy carbon electrode (GC) through the incorporation of hydrochar (HDC) derived from spent coffee grounds and copper nanoparticles (CuNPs) for the detection of ESC in synthetic urine. Characterization of the nanocomposite was conducted using scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), and cyclic voltammetry (CV). The analytical parameters were systematically optimized, and a sensing platform was utilized for the quantification of ESC via square-wave voltammetry (SWV). The established linear range was found to be between 1.0 µmol L−1 and 50.0 µmol L−1, with a limit of detection (LOD) of 0.23 µmol L−1. Finally, an electrochemical sensor was employed to measure ESC levels in synthetic urine, yielding recovery rates ranging from 91.7% to 94.3%. Consequently, the HDC-CuNPs composite emerged as a promising, sustainable, and cost-effective alternative for electroanalytical applications.
Keywords: copper nanoparticles; electrochemical sensor; escitalopram; hydrochar; renewable carbon; spent coffee grounds